In Vivo Imaging of Transiently Transgenized Mice with a Bovine Interleukin 8 (CXCL8) Promoter/Luciferase Reporter Construct - Stellari, Fabio Franco; Franceschi, Valentina; Capocefalo, Antonio; Ronchei, Marcello; Facchinetti, Fabrizio; Villetti, Gino; Donofrio, Gaetano (PLOS ONE, 2012)
One of the most remarkable properties of interleukin 8 (CXCL8/IL-8), a chemokine with known additional functions also in angiogenesis and tissue remodeling, is the variation of its expression levels. In healthy tissues, IL-8 is barely detectable, but it is rapidly induced by several folds in response to proinflammatory cytokines, bacterial or viral products, and cellular stress. Although mouse cells do not bear a clear homologous IL-8 gene, the murine transcriptional apparatus may well be capable of activating or repressing a heterologous IL-8 gene promoter driving a reporter gene. In order to induce a transient transgenic expression, mice were systemically injected with a bovine IL-8 promoter–luciferase construct. Subsequently mice were monitored for luciferase expression in the lung by in vivo bioluminescent image analysis over an extended period of time (up to 60 days). We demonstrate that the bovine IL-8 promoter–luciferase construct is transiently and robustly activated 3–5 hours after LPS and TNF-α instillation into the lung, peaking at 35 days after construct delivery. Bovine IL-8 promoter–luciferase activation correlates with white blood cell and neutrophil infiltration into the lung. This study demonstrates that a small experimental rodent model can be utilized for non-invasively monitoring, through a reporter gene system, the activation of an IL-8 promoter region derived from a larger size animal (bovine). This proof of principle study has the potential to be utilized also for studying primate IL-8 promoter regions.